2015
DOI: 10.1111/bjh.13504
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive characterization of mesenchymal stromal cells from patients with Fanconi anaemia

Abstract: SummaryFanconi anaemia (FA) is an inherited disorder characterized by pancytopenia, congenital malformations and a predisposition to develop malignancies. Alterations in the haematopoietic microenvironment of FA patients have been reported, but little is known regarding the components of their bone marrow (BM) stroma. We characterized mesenchymal stromal cells (MSCs) isolated from BM of 18 FA patients both before and after allogeneic haematopoietic stem cell transplantation (HSCT). Morphology, fibroblast colon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 29 publications
5
22
0
Order By: Relevance
“…1B). These results are in line with the previous studies that show that FA MSCs are defective in their ability to survive in vitro and display spontaneous chromosome breakages [20].…”
Section: Discussionsupporting
confidence: 93%
“…1B). These results are in line with the previous studies that show that FA MSCs are defective in their ability to survive in vitro and display spontaneous chromosome breakages [20].…”
Section: Discussionsupporting
confidence: 93%
“…BM MSC are responsible for bone tissue development and maintenance, and they also give rise to other supporting cell types, including adipocytes and chondrocytes. In FA, only a few studies looked at BM MSC function (using different models and approaches) and showed inconsistent and contradictory results . Some of these studies agreed that FA‐derived BM MSC exhibit cellular deficits, including increased senescence and reduced proliferation, whereas others only found subtle changes in their ability to support hematopoiesis.…”
Section: Discussionmentioning
confidence: 99%
“…48 Several previous studies indicated that MSPC from FA patients display reduced long-term proliferation ability and spontaneous chromosome breakages. 4951 In addition, we have previously reported that MSPC from the murine Fancg − / − model exhibit impaired proliferative capacity. 30 Amarachintha et al .…”
Section: Discussionmentioning
confidence: 99%